2022
DOI: 10.1007/s00277-022-04903-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of C3 with pegcetacoplan results in normalization of hemolysis markers in paroxysmal nocturnal hemoglobinuria

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare, acquired hematologic disorder characterized by complement-mediated hemolysis. C5 inhibitors (eculizumab/ravulizumab) control intravascular hemolysis but do not prevent residual extravascular hemolysis. The newly approved complement inhibitor, pegcetacoplan, inhibits C3, upstream of C5, and has the potential to improve control of complement-mediated hemolysis. The PADDOCK and PALOMINO clinical trials assessed the safety and efficacy of pegcetacoplan in comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…Impressive response rates with hemoglobin levels of 12.14 g/dl (PADDOCK trial, N = 23; NCT02588833) and 13 g/dl (PALOMINO trial, N = 4, NCT 03593200) after 85 days of treatment have also been reported for complement inhibitor naïve patients treated with pegcetacoplan. 120 Sixty-five percent of PADDOCK patients and all of the PALOMINO trial patients became transfusion free. The PRINCE (NCT04085601) phase III trial included 53 patients, who were randomized 2:1, evaluates efficacy and safety of pegcetacoplan compared to purely supportive control treatment including transfusion, anticoagulants and supplements in Ci-naive patients is still awaiting full publication; data published so far do show that 91.4% of patients under pegcetacoplan achieved freedom from transfusions with a median hemoglobin level of 12.8 g/dl at 26 weeks.…”
Section: Pegcetacoplanmentioning
confidence: 99%
See 2 more Smart Citations
“…Impressive response rates with hemoglobin levels of 12.14 g/dl (PADDOCK trial, N = 23; NCT02588833) and 13 g/dl (PALOMINO trial, N = 4, NCT 03593200) after 85 days of treatment have also been reported for complement inhibitor naïve patients treated with pegcetacoplan. 120 Sixty-five percent of PADDOCK patients and all of the PALOMINO trial patients became transfusion free. The PRINCE (NCT04085601) phase III trial included 53 patients, who were randomized 2:1, evaluates efficacy and safety of pegcetacoplan compared to purely supportive control treatment including transfusion, anticoagulants and supplements in Ci-naive patients is still awaiting full publication; data published so far do show that 91.4% of patients under pegcetacoplan achieved freedom from transfusions with a median hemoglobin level of 12.8 g/dl at 26 weeks.…”
Section: Pegcetacoplanmentioning
confidence: 99%
“…While C3‐inhibition results in clinically meaningful blocking of IVH and EVH, we are still lacking evidence that protection from thromboembolic events with proximal complement inhibitions is as effective as terminal inhibition, although preliminary data seem to give some indication that this might be the case 121 . Two cases of thrombosis (one in the setting of diffuse large B‐cell lymphoma and one in the setting of pneumonia) were reported from the 170 patients included into PADOCK, PALOMINO, PEGASUS, and PRINCE 120 …”
Section: Pegcetacoplanmentioning
confidence: 99%
See 1 more Smart Citation
“…Pegcetacoplan appeared generally safe, although drug-related hypersensitivity events occurred in the PADDOCK study. Importantly, there were no thrombotic events or severe infectious complications ( 6 ). Another phase Ib study, the PHAROAH trial (NCT02264639), investigated pegcetacoplan as an add-on therapy in suboptimal responders to eculizumab and demonstrated a hematological improvement, enabling eculizumab discontinuation in 4 subjects ( 7 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The recent FDA approval of several compounds that target the complement system either at the level of the classical pathway (CP) [51,52], the alternative pathway (AP) C3 [53,54], or the terminal pathway C5aR1 [55] and the successful treatment of paroxysmal nocturnal hemoglubinuria (PNH) patients with the terminal pathway inhibiting anti-C5 mAb eculizumab and derivatives [56][57][58] paved the way for an extensive pipeline of new therapeutic inhibitors targeting the complement system at several levels [59][60][61].…”
Section: C5a Receptor Targeting In Neutrophil-driven Diseasesmentioning
confidence: 99%